2020
DOI: 10.3390/app10061929
|View full text |Cite
|
Sign up to set email alerts
|

FEM Simulation of THz Detector Based on Sb and Bi88Sb12 Thermoelectric Thin Films

Abstract: A terahertz (THz) detector based on thermoelectric thin films was simulated using the finite elements method. The thermoelectric circuit consisted of S b and B i 88 S b 12 150-nm films on the mica substrate. S b , B i 88 S b 12 , and mica-substrate properties have been measured experimentally in the THz frequency range. The model of electromagnetic heating was used in order to estimate possible heating of S b - B i 88 S b 12 contact. THz radiation power v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…The multigrid approach utilizes a mesh hierarchy of varying densities. The software algorithm reduces solution time [18][19].…”
Section: Finite Element Methods Simulation Of Guided Wave Phenomena At Terahertz Frequenciesmentioning
confidence: 99%
“…The multigrid approach utilizes a mesh hierarchy of varying densities. The software algorithm reduces solution time [18][19].…”
Section: Finite Element Methods Simulation Of Guided Wave Phenomena At Terahertz Frequenciesmentioning
confidence: 99%
“…The 2D description has been performed using special options: "thin layer" in heat transfer interface and "transition boundary condition" in electromagnetic waves interface. The equations that are used for 2D description are listed in our previous publication [48]. The comparison between temperature change in 2D and 3D case showed that 2D description of film gives a temporal temperature function close to the linear (Figure 7a).…”
Section: The Impact Of Thin Film Description On Temperature Increase Functionmentioning
confidence: 96%
“…Существующие детекторы ТГц-ИК диапазона можно разделить на две группы по принципу работы: фотонные и тепловые [1][2][3][4][5][6][7][8]. В фотонных детекторах излучение поглощается внутри материала путем внутреннего фотоэффекта, т. е. непосредственного взаимодействия фотонов с носителями заряда.…”
Section: Introductionunclassified